Sustainable invesment challenges in emerging markets: Case of India’s NIFTY100ESG indices - Luthfiya, Kyla Alifiya Syahla; Darsono, Susilo Nur Aji Cokro (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
The NIFTY100 ESG Indices in India are influenced by macroeconomic factors such as currency exchange rates, economic policy uncertainty (EPU), CBOE VIX, and global commodity prices like gold and crude oil. Despite the increasing relevance of sustainable investing, limited research has explored how these factors impact ESG-focused indices in emerging markets. This study examines their short- and long-term effects using the Autoregressive Distributed Lag (ARDL) model, analyzing monthly data from January 2019 to December 2024. The findings indicate that in the short term, CBOE VIX, exchange rates, and gold prices negatively affect the index, while gold prices have a positive impact in the long run. Meanwhile, exchange rates, EPU, and crude oil prices show no significant influence. By specifically focusing on India’s ESG investments, this research fills a crucial gap in the literature, moving beyond conventional stock market studies. The results emphasize the importance of strong economic policies and risk management strategies to enhance market stability and promote sustainable investments, offering valuable insights for investors, policymakers, and regulators in an evolving financial landscape.